The Influence of HR Analytics and Perceived Organizational Support on Employee Performance through Employee Engagement in Makassar City - Sudirman Sudirman; Andi Syahrul Makuradde; Rusnathul Amiah; Hadiasman Ibrahim (Economics and Digital Business Review, 2026)
This study aims to examine the effects of Human Resource (HR) Analytics and Perceived Organizational Support (POS) on employee performance, with employee engagement as a mediating variable, in the context of organizations in Makassar City, Indonesia. Grounded in Evidence-Based Management and Social Exchange Theory, this research seeks to provide a comprehensive understanding of how data-driven HR practices and organizational support jointly influence employee outcomes. A quantitative research design was employed using a survey method, with data collected from employees across various organizations in Makassar. The analysis was conducted using Structural Equation Modeling–Partial Least Squares (SEM-PLS) to evaluate both measurement and structural models, including direct and indirect relationships among variables. The findings reveal that HR Analytics and POS have significant positive effects on employee performance, both directly and indirectly through employee engagement. Employee engagement was found to play a substantial mediating role, indicating that the impact of HR Analytics and POS on performance is partially transmitted through enhanced psychological involvement and work-related commitment. Additionally, the model demonstrates strong explanatory power, confirming the robustness of the proposed relationships. This study contributes to the human resource management literature by integrating Evidence-Based Management and Social Exchange Theory into a unified framework, highlighting the interplay between technological and relational factors in shaping employee performance. Practically, the findings suggest that organizations should align data-driven HR practices with supportive organizational environments to foster employee engagement and optimize performance outcomes. Keyword : HR Analytics, Perceived Organizational Support, Employee Performance through Employee